Reasons for Staying With Your Employer: Identifying the Key Organizational Predictors of Employee Retention Within a Global Energy Business. Issue 4 (April 2020) - Steiner, Sarah; Cropley, Mark; Simonds, Laura; Heron, Richard
Abstract : Objective: Drawing upon the social exchange theory, this study developed and tested a theoretical model to identify factors predicting intentions to stay within a global energy business. Methods: Structural equation modeling was applied to an annual employee survey ( N  = 30, 094). Results: The most significant factors predicting intention to stay were organizational engagement (when employees are seen to role model company values and behaviors) and relationship with supervisor (when "my manager treats me fairly"). Perceived supervisor support (when employees believe that the company "really cares about my health and well-being") and communication significantly predicted both work engagement and organizational commitment. Conclusion: When employees believe that their supervisor is concerned about their well-being, recognizes their contributions, and role-models the organization's values, they reported more engagement and a stronger commitment to remain with the organization.